Autotaxin Inhibition with PF-8380 Enhances the Radiosensitivity of Human and Murine Glioblastoma Cell Lines - Bhave, Sandeep R.; dadey, David Y.; Karvas, Rowan M.; Ferraro, Daniel J.; Kotipatruni, Rama P.; Jaboin, Jerry J.; Hallahan, Andrew N.; DeWees, Todd A.; Linkous, Amanda G.; Hallahan, Dennis E.; Thotala, Dinesh (Frontiers in Oncology, 2013)
Purpose: Glioblastoma multiforme (GBM) is an aggressive primary brain tumor that is radio-resistant and recurs despite aggressive surgery, chemo and radiotherapy. Autotaxin (ATX) is over expressed in various cancers including GBM and is implicated in tumor progression, invasion, and angiogenesis. Using the ATX specific inhibitor, PF-8380, we studied ATX as a potential target to enhance radiosensitivity in GBM. Methods and Materials: Mouse GL-261 and Human U87MG cells were used as GBM cell models. Clonogenic survival assays and tumor transwell invasion assays were performed using PF-8380 to evaluate role of ATX in survival and invasion. Radiation dependent activation of Akt was analyzed by immunoblotting. Tumor induced angiogenesis was studied using the dorsal skin-fold model in Gl-261. Heterotopic mouse GL-261 tumors were used to evaluate the efficacy of PF-8380 as a radiosensitizer. Results: Pretreatment of GL-261 and U87-MG cells with 1µM PF-8380 followed by 4Gy irradiation resulted in decreased clonogenic survival, decreased migration (33% in GL-261;P = 0.002 and 17.9% in U87; P = 0.012) decreased invasion (35.6% in GL-261; P = 0.0037 and 31.8% in U87; P = 0.002), and attenuated radiation induced Akt phosphorylation. In the tumor window model inhibition of ATX abrogated radiation-induced tumor neovascularization (65%; P=0.011). In a heterotopic mouse GL-261 tumors untreated mice took 11.2 days to reach a tumor volume of 7000 mm3 , however combination of PF-8380 (10mg/kg) with irradiation (5 fractions of 2Gy) took more than 32 days to reach a tumor volume of 7000 mm3 . Conclusion: Inhibition of ATX by PF8380 led to decreased invasion and enhanced radiosensitization of glioma cells. Radiation induced activation of Akt was abrogated by inhibition of ATX. Furthermore, inhibition of ATX led to diminished tumor vascularity and delayed tumor growth. These results suggest that inhibition of ATX may ameliorate glioblastoma response to radiotherapy.